Designing and Implementing a Cat Runner Game Using Scratch 3 - Eldo, Handry; Yanti, Irma; Naurah, Risky Indah (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
In the current information era, the rapid development of technology follows the development of science and technology. Likewise, multimedia applications are developing very rapidly, especially in the smartphone sector, the use of smartphones is now not only used as a communication medium. Smartphones are then used as a means of entertainment, one of which is for playing games. Games have become one of the complementary applications on smartphones, one of which is Android-based games. The advantage of playing games on smartphones is that players can play games wherever and whenever they want. This Cat Runner game is a game about a cat that has 3 lives, where this game is played by the cat jumping to catch butterflies and avoiding rockets so that its life doesn't decrease. If this cat is hit by rockets 3 times it will die. This game is an entertainment themed game that can be played by children under five years old. This game was built using the Scratch 3 application. We use smartphones and websites as a platform to run this game.